Characterization of pregnant women with positive rapid hiv test in Fortaleza-CE - Léa Maria Moura Barroso; Zenilda Vieira Bruno; Marta Maria Soares Herculano; Marli Teresinha Gimeniz Galvão (Rev Rene)
The study aimed to characterize pregnant women submitted to the rapid HIV test in a maternity in Fortaleza, State of Ceará. As for the sociodemographic and clinic characteristics. it was a Transverse study of the retrospective documental type, with thirteen pregnant women with positive rapid HIV test, from April 2002 to April 2004. The pregnant women were 26.2 years old on average; 61,5% and had gone to school for about four to seven years; 69,2% were from the capital and 30,8% from the ;the country side; 53,8% were housewives, 54,0% had undergone from four to seven prenatal consultations, 46,2% had discovered the infection before childbirth, 84,6% received the prophylaxis just at childbirth, 46,0% of them had the time of broken bag up to four hours, 77,0% surgical childbirth and all the newborns had received the syrup of AZT in the first two hours of life. We concluded that the institution implemented the recommendations to guarantee the reduction of the risk of newborn’s contamination. It was observed that there is deficiency for reduction of vertical transmission in the services that offered prenatal care previous to the childbirth.